2018
DOI: 10.1080/20002297.2018.1549931
|View full text |Cite
|
Sign up to set email alerts
|

Aggregatibacter actinomycetemcomitansLPS binds human interleukin-8

Abstract: Various gram-negative species sequester host cytokines using outer membrane proteins or surface modulation by sulfated polysaccharides. An outer membrane lipoprotein (BilRI) of the periodontal pathogen Aggregatibacter actinomycetemcomitans binds several cytokines, including interleukin (IL)-8. Because IL-8 is positively charged at physiological pH, we aimed to determine whether IL-8 interacts with negatively charged lipopolysaccharide (LPS). Binding was investigated using electrophoretic mobility shift assays … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…After challenge with the A. actinomycetemcomitans biofilm, the levels of CXCL1, CXCL8, and CCL2 were lower than in the control (Figure ). Previously, it was found that A. actinomycetemcomitans can sense and bind cytokines; among them was CXCL8 (T. Ahlstrand et al, ; T. Ahlstrand et al, ; T. Ahlstrand, Kovesjoki, Maula, Oscarsson, & Ihalin, ). Lower metabolic activity of biofilms induced by cytokine binding could lead to higher resistance (A. Paino et al, ) and could reduce the production of virulence factors providing an explanation why the peri‐implant mucosa was not impaired after challenge with the A. actinomycetemcomitans biofilm.…”
Section: Discussionmentioning
confidence: 99%
“…After challenge with the A. actinomycetemcomitans biofilm, the levels of CXCL1, CXCL8, and CCL2 were lower than in the control (Figure ). Previously, it was found that A. actinomycetemcomitans can sense and bind cytokines; among them was CXCL8 (T. Ahlstrand et al, ; T. Ahlstrand et al, ; T. Ahlstrand, Kovesjoki, Maula, Oscarsson, & Ihalin, ). Lower metabolic activity of biofilms induced by cytokine binding could lead to higher resistance (A. Paino et al, ) and could reduce the production of virulence factors providing an explanation why the peri‐implant mucosa was not impaired after challenge with the A. actinomycetemcomitans biofilm.…”
Section: Discussionmentioning
confidence: 99%
“…LPS was isolated from A. actinomycetemcomitans cells harvested from 12 blood agar plates, using a combination of procedures [48,49], as described [35]. LPS preparations were resuspended in 100 µl H 2 O and the yield (typically 1.5-2.8 × 10 6 endotoxin units [EU]) was estimated using the ToxinSensor™ chromogenic Limulus Amebocyte Lysate (LAL) endotoxin kit (BioNordika, Sweden).…”
Section: Isolation Of Lpsmentioning
confidence: 99%
“…Lipopolysaccharide (LPS) is one of the most abundant components of OMVs, including those released by A. actinomycetemcomitans, and is displayed on the outer surface of the vesicles [23][24][25]. It was recently shown that LPS is involved in the binding of IL-8 by A. actinomycetemcomitans OMVs [35], and it cannot be excluded that the LPS in OMVs also may interact with complement. The serotype-specific polysaccharide (S-PA) determinant of A. actinomycetemcomitans resides in the LPS O antigen, which is immunodominant [36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…It has also been demonstrated that A. actinomycetemcomitans OMVs can carry small molecules, including lipopolysaccharide (LPS), which can interact with complement [93]. LPS may also play a role in the observed binding of A. actinomycetemcomitans OMVs to IL-8 [94]. Evidence that A. actinomycetemcomitans OMVs carry NOD1- and NOD2-active peptidoglycan, which can be internalized into non-phagocytic human cells including gingival fibroblasts [19], reveals a role of the vesicles as a trigger of innate immunity.…”
Section: Outer Membrane Vesiclesmentioning
confidence: 99%